2017
DOI: 10.1111/ejn.13739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forced, passive, and voluntary exercise on spinal motoneurons changes after peripheral nerve injury

Abstract: After peripheral nerve injury, there are important changes at the spinal level that can lead to disorganization of the central circuitry and thus compromise functional recovery even if axons are able to successfully regenerate and reinnervate their target organs. Physical rehabilitation is a promising strategy to modulate these plastic changes and thus to improve functional recovery after the damage of the nervous system. Forced exercise in a treadmill is able to partially reverse the synaptic stripping and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…SYN is a synaptic marker that labels almost all axon terminals. A previous study 29 reported that many axon terminals, except of primary afferent neurons, recover from withdrawal of synaptic input, which is also consistent with our results.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…SYN is a synaptic marker that labels almost all axon terminals. A previous study 29 reported that many axon terminals, except of primary afferent neurons, recover from withdrawal of synaptic input, which is also consistent with our results.…”
Section: Discussionsupporting
confidence: 94%
“…[17][18][19][20][21][22][23][24][25] Promoting axonal regeneration facilitates reinnervation of the NMJ, 26 and enhancing afferent input to motor neurons via exercise reconnects primary afferents and motor neurons that have withdrawn because of the modulation of spinal cord changes, reestablishing synaptic function. [27][28][29] A planned peripheral nerve insult (conditioning lesion [CL]) promotes the axonal regeneration of peripheral nerves in response to subsequent nerve damage. 30 It has been reported that after repeated peripheral nerve injury by CL, the time from injury to the onset of regeneration is shortened, 31 and the rate of axonal outgrowth 32,33 and the number of regenerating axons 34 are increased.…”
mentioning
confidence: 99%
“…Conversely, the LICT also could not promote significant changes in microglia morphology, indicating that HIIT rather than LICT is a highly effective strategy to improve neuroinflammation in the brain compared to CT [62]. Additionally, Arbat-Plana observed that higher intensity protocols reduced microglia reactivity to modulate the spinal changes after nerve damage [5]. Therefore, the differences in neuroinflammation response can be explained by differences in the amount of stress induced by the different protocols of physical activity.…”
Section: Discussionmentioning
confidence: 97%
“…There is increasing evidence of exercise having beneficial regenerative, rehabilitative, and neuro-plasticity-associated effects in central and peripheral nervous systems (Park and Höke, 2014;Arbat-Plana et al, 2017;Theisen et al, 2017). Additionally, exercise has been linked with possible neurotrophic factor signaling regulation, as reviewed by Cobianchi et al (2017) and Cintrón-Colón et al (2020).…”
Section: Exercise As a Complementary Treatmentmentioning
confidence: 99%